12-state multi-level cell storage implemented in a 128 Mb phase change memory chip. Issue 23 (1st April 2021) - Song, Zhitang; Cai, Daolin; Cheng, Yan; Wang, Lei; Lv, Shilong; Xin, Tianjiao; Feng, Gaoming
Abstract : 128 Mb Phase Change Memory (PCM) chips show potential for many applications in artificial intelligence. Abstract : 128 Mb Phase Change Memory (PCM) chips show potential for many applications in artificial intelligence. A PCM cell often has a sandwich structure that consists of a TiN bottom electrode, a phase change material, and a top metal. TiN films prepared by atomic layer deposition have high thermal stability, and a WN coating layer on the TiN electrode can prevent oxidation in the electric and thermal field, achieving high endurance of the TiN electrode over 10 11 cycles. In the phase change material of carbon-doped Ge2 Te2 Te5 (CGST), C–C chains and C clusters precipitate at the Ge2 Te2 Te5 (GST) grain boundaries, which effectively refines the grain size of GST. The C confinement enhances the Ge/Sb atomic migration barrier and suppresses the composition segregation in the Reset/Set operation process and the atomic relaxation of the CGST material. As a result, the endurance and conductivity-drift of the PCM chip were enhanced. Finally, stability over 5 × 10 8 cycles and 12 multi-level stable states were achieved in the 128 Mb PCM chip. This work presents a step towards the realization of large-scale and energy-efficient neuromorphic computing systems.